Textile Dye Reactive Black 5 (RB5) Bio-Sorption with Moving Bed Biofilm Reactor and Activated Sludge - Suryawan, I Wayan Koko; Helmy, Qomarudin; Notodarmojo, Suprihanto; Pratiwi, Riska; Septiariva, Iva Yenis (Indonesian Journal of Environmental Management and Sustainability, 2021)
Reactive Black 5 (RB5) is one of the dyes used in textile industries in Indonesia. However, the high color content can interfere with the condition of water bodies if not treated. This waste treatment process is usually treated with biological treatment processes. Biological processing often used is the MBBR unit and activated sludge. This study aims to determine the RB5 dye’s bio-sorption efficiency using MBBR processing and activated sludge. MBBR processing and activated sludge consist of seeding, acclimatization, and running stages. This research was carried out using a real textile wastewater approach by adding 100 mg/L RB5 and adding 1000 mg/L starch solution. The processing results of the seeding stage indicate increasing in biomass. The acclimatization stage with 50% and 75% of wastewater indicates increased biomass and color removal. The RB5 color removal efficiency results in the MBBR unit and activated sludge show 41% and 84% values. The MBBR processing shows fluctuations each time where the desorption process occurs in the color removal. For this reason, the ozone pre-treatment process is conducted in the MBBR unit. The integrated pre-treatment with MBBR results show the same fluctuation as the previous processing with a color removal efficiency of 43% with a color removal efficiency of 43%.